(untitled) (Journal of Partial Differential Equations, 2020)
In this paper we prove the existence of a positive solution to the following superlinear elliptic Dirichlet problem, - &#931^n_i,j=1aij(x, u, Du)D_iju = f(x, u, Du) in &#937, u = 0 on &#8706&#937 where f satisfies certain growth conditions.